(untitled) (Ciudades, 2017)
Located into the heart of the town, the Croix-Petit neighbourhood is one of the first buit-up areas of the New Town of Cergy-Pontoise. The original urban project aimed to design a working-class neighbourhood which could benefit from equipments and urban amenities. The first decade showed a success but the area has started to decline from the 80’s onwards. From January 2002, the municipality decided to launch a vast renewal work. The state subsidies aimed to achieve huge renewal work in a tabula rasa rational. The goal is also to change the residential bid – social mix ideology - to recover the stigmatised part of the city which put prejudice of the whole city. This paper is about how households react to the decline of their neighbourhood and to the way it is radically transformed. Our raw material comes from direct interviews with households who have beneficiated from re-housing process. The way inhabitants have faced urban renewal can be underlined. It is fairly striking that households did not manage to develop a structure to stand up to problems they have met. This lack of structured reaction has lead to believe in the pressing need of renewal. In the end, it will be necessary to question the practices developed during the urban operations, in the French context. These take place generally in a Top-down way, leaving no place to the capacities of mobilization of the resident populations. These approaches which remain widely dominant are now the object of increasing criticisms.